Analysis of Novelty Elements as a Requirement for Patent Registration in Law Number 13 of 2016 Concerning Patents - Putu Ayu Ira Kusuma Wardani; Desak Putu Dewi Kasih; I Made Arya Utama (Journal of World Science, 2024)
This study delves into the elements of patent rights and dispute resolution strategies in cases of patent infringement. The background of the research stems from the necessity to understand the legal framework surrounding patent protection and the mechanisms available for resolving disputes in the event of infringement. The primary objective is to identify the crucial components of patent rights and the various methods employed to address disputes arising from alleged patent violations. Employing a normative legal research approach, with both conceptual and statutory analyses, this study aims to provide a comprehensive overview of the subject matter. The findings underscore the significance of novelty as a fundamental criterion for patent acceptance, as defined by Law Number 13 of 2016 concerning Patents. Novelty, characterized by the absence of prior public disclosure, usage, or inclusion in existing knowledge standards, is essential for patent registration. The study reveals that patent disputes concerning novelty can be addressed through diverse legal avenues, including patent removal suits, trial proceedings, mediation, patent reexamination, out-of-court settlements, and appellate processes. Furthermore, alternative mechanisms such as arbitration offer additional pathways for resolving disputes. The implications of this research highlight the importance of adhering to novelty requirements during patent registration and understanding the array of dispute resolution mechanisms available to safeguard intellectual property rights.